The Application of Reminiscence Therapy in Efforts to Prevent Dementia in the Elderly - Wimar Anugrah Romadhon; Suprajitno; Ning Arti Wulandari; RR Dewi Rahmawaty (STIKes Patria Husada Blitar, 2023)
Elderly at risk of dementia caused by decrease in cognitive function, one of the treatments that is safe with no side effects is the reminiscence therapy to increase cognitive function. The purpose of this study was to explain the reminiscence therapy on level of dementia in the elderly. The design of this study was pre-experimental design. The population was elderly in PSTW Wlingi. The total sample was 15 respondents. The sampling technique was purposive sampling with the inclusion criteria of cooperative elderly, easy to communicate with and willing to become respondents. The independent variable was the reminiscence therapy which was carried out for 6 times in a week, the dependent variable was level of dementia. The data was collected by using MMSE (Mini Mental State Examination) questionnaires and analyzed by using Paired t-test with a significance level of α ≤0.05. The reminiscence therapy to decrease level of dementia on elderly (p = 0.000). There was a significant difference between pre intervention and post intervention of the reminiscence therapy. The reminiscence therapy can improve cognitive function with dementia in the elderly. Elderly can apply the reminiscence therapy to help them memories and as support nursing intervention. The future studies could add to the respondents and determine the factors according to the characteristic of respondent.